The Impact of Road Infrastructure Development Sourced from the Special Allocation Fund for the Thematic Road Sub-Sector of Food Estate Development in 2024 on the Development of Meranti District, Asahan Regency - Ramadhan, Joko; Nuraini, Cut (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines the impact of road infrastructure development funded by the Special Allocation Fund for the thematic road sub-sector on the development of Meranti District, Asahan Regency, in 2024. Using a qualitative approach with purposive sampling, data were collected through interviews with informants meeting specific criteria. The findings reveal that improved road infrastructure positively influences accessibility, community welfare, and local economic growth, contributing to sustainable development. Continued investment in infrastructure and community involvement in planning and management are essential to ensure equitable benefits for all.